Complication tardive d'un traitement chirurgical par interposition prothétique d'une coartation aortique: rupture d'un faux anévrisme anastomotique traitée par implantation endoluminale d'endoprothèse couverte - Vařejka, Petr; Lubanda, Jean-Claude; Procházka, Pavel; Heller, Samuel; Beran, Stanislav; Dostál, Ondřej; Charvát, František; Hořejš, Josef; Semrád, Michal; Linhart, Aleš (Journal des maladies vasculaires, 2010)
Aortic coarctation is a frequent congenital defect requiring early surgical treatment. Late complications of these surgical procedures can be fatal as in the case of a ruptured anastomotic pseudoaneurysm. We present a case of a 49-year-old man presenting with hemorrhagic shock due to this complication who was successfully treated by endovascular techniques with implantation of two stent grafts. This case illustrates the fact that endovascular aortic repair is feasible, certainly less invasive and very efficient for this type of complication when used in an experienced center.
Keywords: Aneurysm, False; Time Factors; lidé středního věku; Aortic Rupture; Postoperative Complications; lidé; koarktace aorty; časové faktory; Middle Aged; Aortic Aneurysm, Thoracic; Blood Vessel Prosthesis; aneurysma hrudní aorty; Aortic Coarctation; Male; nepravé aneurysma; Humans; mužské pohlaví; ruptura aorty; cévní protézy; pooperační komplikace